The relationship of general retention ability to new South African group test non-verbal/verbal IQ discrepancies and their academic correlates - Watson, Peter James (Rhodes University, Faculty of Education, Department of Education, 1992)
Both experimental research (Robbertse,1952)and clinical observation (Kruger, 1972; van der Merwe,1978) have indicated that pupils with a Verbal IQ score 10 or more points lower than their non-Verbal IQ (termed a 'Type 1' discrepancy in the present research) on the New South African Group Test (NSAGT) show poorer academic achievement than their peers of similar ability. The present research investigates the relationship of general retention ability, as defined by Hakstian and Cattell (1978), to Type 1 discrepancies as well as to their academic correlates. One hundred and thirty-nine standard seven English-speaking boys were tested on the NSAGT and the Junior Aptitude Test (JAT) (of which tests 8 and 9 give an indication of general retention ability) and divided into a group with Type 1 discrepancies and two control groups. All three groups were matched on full-scale IQ. Comparison of these three groups, using the analysis of variance technique, showed that there was no significant difference between them in level of general retention ability or in academic performance (measured by average percentage in the final standard seven examination). While no significant difference was found between the three groups regarding the relationship of general retention ability to academic performance, in the Type 1 discrepancy group the relationship of rote memory (JAT test 8) to academic performance differed markedly from that of associative memory (JAT test 9) to academic performance. In the Type 1 discrepancy group rote memory was highly associated with academic performance, possibly indicating a compensatory strategy for the lower Verbal ability in this group, enabling it to achieve academically on par with the control groups, contrary to what would be expected on the basis of Robbertse's (1962) findings. In terms of Jensen's (1982) Level 1/Level 11 theory of intelligence, it appears from the present research that rote memory ability (JAT test 8) varies between being a Level 11 ability (in the Type 1 discrepancy group) to acting as a Level 1 ability in the two control groups. The present research questions Verwey and Wolmarans's (1980) description of both JAT tests 8 and 9 as simple measures of retention Test 9, in particular, appears to function consistently as a Level 11 ability.
Keywords: Intellect Intelligence tests -- South Africa; Academic achievement -- South Africa